Três diferentes abordagens de modelagem e simulação do processo de cristalização na produção de açúcar no simulador EMSO - Marciniuk Junior, Melécio (Universidade Federal de São Carlos, 2015)
Brazil is the largest producer of cane sugar and the largest producer and exporter of sugar being the state of São Paulo the responsible for over 60% of the national production of sugar, and the region is where is located the city of São Carlos is main producer region of Brazil, this fact becomes a motivation for this project. The crystallization process is the most important in the production of sugar and responsible for the quality of the final product. This work deals with the modeling and simulation of this process through three different approaches: the ideal crystallizer (MSMPR), the integrated sugar production without description of crystals, approach called "gray-box", and the industrial crystallizer. The models were developed in the software EMSO. The EMSO is a program developed in Brazil and has a great advantage compared to other programs, it's a free program, without the need to license purchase. By allowing full access to the developed mathematical models, facilitates the insertion of new models such as the present study about crystallization and allow the improvement of existing models, allowing also the development of specific software libraries. The first held approach, MSMPR, aims to introduce a protocol currents description containing solids and the crystallization process in the EMSO, for in his library there is no model that describes the crystallization or even containing solids, unlike other widely used commercial programs for the simulation of processes such as Aspen Plus, having a model MSMPR. So when performing this first approach, the EMSO can match other programs in relation to the crystallization process. The mass averaged crystal size (MA) obtained with the parameters set as default, L43 = 1.18 mm is much greater than the expected value L43 = 0.5 to 0.55 mm, but with the variation of the kinetic parameters can be obtained results within the desired range . The second approach is a simplified model called "gray-box" in order to facilitate the paying in of crystallization models with models referring to others process. The sugar production obtained in this model was similar than that reported in the literature, but the model can be useful in paying in of process models which constitute a industrial plant. The third and most important approach corresponds to the model of an industrial crystalliser with intent to represent real process of sugar production using data from literature. The discussion was carried out on the variables: temperature, brix, crystal mass and MA. The variations of temperature and brix relative to time obtained are consistent with each step of the process. The crystal mass produced in the simulation is approximately 50% lower than that found in the literature, whereas the MA is also below, but achieves excellent results in the change of the kinetic parameters. The final results obtained in the simulations do not coincide with the expected results, but the easy access to developed models makes these models a good instrument to parameters analysis, reaching with some changes in the kinetic parameters, in satisfactory results that well represent the real process.
Keywords: Cristalização; Açúcar; EMSO; Modelagem da cristalização; MSMPR; Crystallization; Sugar; EMSO; Crystallization modeling; MSMPR; CIENCIAS EXATAS E DA TERRA